Consumption of Spicy Food and Caffeinated Drinks in Culinary Concentration PKK Students - Diza, Salsabila Mutiara; Kasmita, Kasmita; Yuliana, Yuliana; Mustika, Sari (Universitas Negeri Padang, 2024)
The aim of this research is to describe the consumption of spicy food and caffeinated drinks among PKK Culinary Concentration students based on research indicators. The indicators in this research are the type of food and drink, the amount of food and drink and the frequency of consumption of the food and drink. The type of research used is quantitative descriptive, the data source in this research is PKK students with a culinary concentration, totaling 114 respondents. The data collection technique used was to fill out a questionnaire (google form) to obtain complete and clear information about the consumption of spicy food and caffeinated drinks among PKK students with a culinary concentration. The research results show that on average PKK Culinary Concentration students consume spicy food with a frequency of 1-2 times/week (43%) with the amount consumed being 1 portion (79%) and how to get it. food is by buying it (78%). ), while the average consumption of caffeinated drinks with a frequency of 1-2 times/week is (35%) with consumption of 1 serving is (70%) and the way to get this food is to buy it (56%). From the research results, it can be interpreted that the consumption of spicy food and caffeinated drinks among PKK Culinary Management Concentration students is still within safe limits.